Peran mediasi etos kerja Islami antara praktik human resource dan kinerja organisasi pada lembaga keuangan syariah - Wahid Wachyu Adi Winarto (Jurnal Ekonomi Modernisasi, 2021)
This study aims to analyze the relationship between human resource practices which include recruitment and selection, training and development, compensation, performance, employee participation on organizational performance with Islamic work ethic as a mediating variable in Islamic financial institutions. The research approach uses quantitative methods and the research sample is employees and staff at Islamic financial institutions in Pekalongan as many as 97 respondents. Data analysis using Smart PLS to test direct and indirect relationships between variables. The findings in this study are that there is a significant positive direct relationship between human resource practices on organizational performance, human resource practices on Islamic work ethic, and Islamic work ethic on organizational performance. In addition, there is also a significant positive result of the indirect relationship between human resource practices and organizational performance mediated by Islamic work ethic. In terms of managerial implications, that human resource practices are positively related to Islamic work ethics in every job as an effort to improve organizational performance. In particular, Islamic work ethics as the behavior and thoughts of employees must be developed and improved and can be a concern of the organization. Recommendations for further research by adding other instruments to human resource practice include management discipline, employee health and safety.